Effect of magnesium on vascular calcification in chronic kidney disease patients: a systematic review and meta-analysis - Ya Zhan; Rongjia Zhang; Guisen Li (Renal Failure)
Purpose To evaluate the effects of magnesium (Mg) supplementation on vascular calcification (VC) in patients with chronic kidney disease (CKD).Methods PubMed, Embase, Cochrane Library, Medline, Web of Science, CNKI, VIP, and WanFang databases were searched from build to July 2022. Randomized controlled trials (RCT) and non-RCT related to whether Mg supplementation inhibits VC in patients with CKD were included. The literature was screened according to inclusion and exclusion criteria, and quality evaluation and data collection were performed. Meta-analysis was performed using Review Manager 5.4 software.Results 8 RCTs and 1 non-RCT studies with a total of 496 patients were eventually included. Compared to control groups, Mg supplementation increased serum Mg levels (SMD = 1.26, 95% CI: −0.70 to 1.82, p < 0.001), but it was not statistically significant in alleviating the degree of VC, increasing T50, and reducing serum phosphorus (P) levels in patients with CKD (all p > 0.05). Oral Mg reduced left (WMD=−0.06, 95% CI. −0.11 to −0.01, p = 0.03) and right (WMD=−0.07, 95% CI: −0.13 to −0.01, p = 0.02) carotid intima-media thickness (cIMT). Additionally, calcium (Ca) (SMD=−0.43, 95% CI: −0.74 to −0.11, p = 0.008) and parathyroid hormone (PTH) (SMD=−0.43, 95% CI: −0.75 to −0.11, p = 0.008) levels were reduced by increasing dialysate Mg concentration.Conclusions Mg supplementation increased serum Mg levels and reduced Ca, PTH, and cIMT, but it did not reduce VC scores in patients with CKD. This still requires further studies with larger samples to evaluate the effect of Mg supplementation on VC.